Demographic and migration processes of large cities of Kazakhstan: Main trends and dynamic (Journal of Geography and Environmental Management, 2025)
Natural and migration movement of the population are indicators of all social, economic, geopolitical and other changes occurring in society. In the last decades, one of the tendencies of the development of population in the Republic of Kazakhstan has been the rapid growth of large urban agglomerations of the country due to concentration of a substantial number of the population in them. The spatial concentration of a large population provides both a number of advantages and also has negative challenges and threats. This article provides a comparative analysis of the development of demographic processes in Kazakhstan’s three large cities (Astana, Almaty and Shymkent) for the period from 2000 to 2022. An assessment of the migration processes occurring in three cities was carried out, trends in external and internal migration of cities and the reasons behind them were identified. Understanding the essence of demographic and migration processes allows us to evaluate and predict economic trends and trends in the development of social infrastructure of regions. Analysis of the population structure is an important condition for developing the fundamental directions of the country's socio-economic and demographic policy. The analysis was based on the statistical data from the Bureau of National Statistics of the Republic of Kazakhstan.
Keywords: demographic processes; fertility; mortality; population migration; large cities of Kazakhstan